Circulatory Anomalies - Preston Scott Cohen (Oz, 2004)
In the following projects, conflicts between architecture and geometry are resolved by unanticipated forms and functional scenarios. The resolution of discordance requires a synthesis that produces hyper coherency, an unanticipated regulative principle that reabsorbs the anomalies.